Liquid crystal alignment agent, liquid crystal alignment film, and liquid crystal display element using the same

By using a liquid crystal alignment agent composed of polymer (A) and polymer (B), the problems of charge accumulation and relief in the FFS-based liquid crystal display element are solved, and the display performance is improved.

CN113168054BActive Publication Date: 2025-03-04NISSAN CHEM CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN201980080517.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-12-06
Filing Date
2019-12-05
Publication Date
2025-03-04
Estimated Expiration
2039-12-05

AI Technical Summary

Technical Problem

FFS-based liquid crystal display elements are prone to charge accumulation problems, and the accumulated charge is unfast, resulting in a degradation of display performance.

Method used

The polymer obtained by reacting a tetracarboxylic acid derivative with a diamine is used to prepare a liquid crystal alignment film to improve the display performance of the liquid crystal display element.

Benefits of technology

The FFS-type liquid crystal display element has achieved a small amount of charge accumulation and a quick charge accumulation effect, which improves the display performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113168054B_ABST
    Figure CN113168054B_ABST
Patent Text Reader

Abstract

The present invention provides a liquid crystal alignment agent, a liquid crystal alignment film, and a liquid crystal display element that can obtain a liquid crystal alignment film with a fast relaxation of accumulated charges and a small amount of accumulated charges. The liquid crystal alignment agent of the present invention contains the following polymer (A) and polymer (B). Polymer (A): A polymer obtained by the reaction of a tetracarboxylic acid derivative component with a diamine component comprising a diamine represented by the following formula (1) and a diamine represented by the following formula (2). Polymer (B): A polymer obtained by the reaction of a tetracarboxylic acid derivative component with a diamine component comprising at least one of the diamines represented by the following formula (3). Wherein, Y2 is a divalent organic group having a nitrogen atom bonded to an aromatic group or a nitrogen-containing aromatic heterocycle. H2N‑Y2‑NH2 (3)
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a liquid crystal aligning agent, a liquid crystal aligning film obtained from the liquid crystal aligning agent, and a liquid crystal display element including the obtained liquid crystal aligning film. Background Art

[0002] Liquid crystal display elements are widely used as display parts of personal computers, mobile phones, smart phones, televisions, etc. Liquid crystal display elements include, for example: a liquid crystal layer, which is sandwiched between an element substrate and a color filter substrate; pixel electrodes and common electrodes, which apply an electric field to the liquid crystal layer; a liquid crystal orientation film, which controls the orientation of liquid crystal molecules in the liquid crystal layer; and a thin film transistor (TFT: Thin Film Transistor), which switches the electrical signal supplied to the pixel electrode, etc. As a driving method for liquid crystal molecules, known are: longitudinal electric field methods such as TN (Twisted Nematic) method and VA (Vertical Alignment) method; and transverse electric field methods such as IPS (In-Plane Switching) method and FFS (Fringe Field Switching) method. Among them, compared with the longitudinal electric field method, the transverse electric field method in which the liquid crystal molecules switch parallel to the substrate has a wide viewing angle characteristic, and is also known as a liquid crystal display element capable of high-quality display.

[0003] As factors that affect the display quality level of liquid crystal elements, the uniformity of liquid crystal orientation, the voltage holding rate of liquid crystal cells, and the charge accumulation characteristics are known. For example, when the voltage holding rate is low, sufficient voltage cannot be applied to the liquid crystal, and the display contrast is reduced. In addition, when charges accumulate in the liquid crystal cell, the orientation of the liquid crystal is disturbed, or afterimages and ghosting are caused, which significantly reduces the display quality level of the liquid crystal element.

[0004] In particular, compared with the longitudinal electric field method, the transverse electric field method has fewer electrodes formed in the substrate, so the voltage holding ratio is likely to decrease, or the distance between the pixel electrode and the common electrode is close, so a strong electric field acts on the alignment film and the liquid crystal layer, so that charges are easily accumulated, etc., and the undesirable conditions caused by the insufficient voltage holding ratio and charge accumulation characteristics are likely to become significant. In addition, in the transverse electric field method, if the orientation restriction force of the liquid crystal is weak, when the liquid crystal is driven for a long time, the liquid crystal cannot return to the initial orientation state, resulting in a decrease in contrast or becoming a cause of afterimages, so the orientation restriction force of the liquid crystal alignment film also becomes important.

[0005] With respect to the above-mentioned problem of the transverse electric field method, a method of using a liquid crystal aligning film obtained from a liquid crystal aligning agent obtained by mixing a highly oriented polymer and a low-resistance polymer has been proposed (Patent Document 1).

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: International Publication No. WO2004 / 53583 Pamphlet Summary of the invention

[0009] Problems to be solved by the invention

[0010] The properties required of the liquid crystal alignment film have become stricter as the performance of the liquid crystal display element has become higher. In particular, even compared with the IPS method, which is also a transverse electric field method, the FFS method has a structure in which charges are easily accumulated in the liquid crystal unit and the accumulated charges are not easy to escape. Therefore, for example, not only the suppression of charge accumulation, but also the rapid relaxation of the accumulated charges have become important. In addition, the electric field strength of the FFS method is greater than that of the IPS method, so the requirements related to the orientation restriction force of the liquid crystal are also strict.

[0011] Based on the above situation, the problem of the present invention is to provide a liquid crystal alignment agent, which can obtain a liquid crystal alignment film suitable for a liquid crystal display element of a transverse electric field method, especially a FFS method, and further can obtain a liquid crystal alignment film with a small amount of charge accumulation and a fast relaxation of the accumulated charge even in the FFS method.

[0012] Solutions for solving problems

[0013] The present inventors have conducted intensive studies to achieve the above-mentioned object, and as a result, have found that the above-mentioned object can be achieved by the invention of the following gist.

[0014] A liquid crystal aligning agent comprising the following polymer (A) and polymer (B).

[0015] Polymer (A): A polymer obtained by reaction of a tetracarboxylic acid derivative component with a diamine component containing a diamine represented by the following formula (1) and a diamine represented by the following formula (2).

[0016]

[0017] Polymer (B): A polymer obtained by reaction of a tetracarboxylic acid derivative component and a diamine component containing at least one diamine represented by the following formula (3).

[0018] H2N-Y2-NH2 (3)

[0019] (Y2 is a divalent organic group having a nitrogen atom or a nitrogen-containing aromatic heterocycle bonded to an aromatic group.)

[0020] Effects of the Invention

[0021] According to the present invention, it is possible to improve the display performance of a transverse electric field liquid crystal display element, and in particular, improve the display performance of an FFS liquid crystal display element in which the amount of charge accumulation is small and the relaxation of the accumulated charge is fast. DETAILED DESCRIPTION

[0022] Both the polymer (A) and the polymer (B) used in the present invention are polymers obtained by reaction of a tetracarboxylic acid derivative component and a diamine component.

[0023] As an example of a tetracarboxylic acid derivative, tetracarboxylic dianhydride, tetracarboxylic acid disilyl ester, dichlorinated tetracarboxylic acid, tetracarboxylic acid dialkyl ester, tetracarboxylic acid diene ester, dichlorinated tetracarboxylic acid dialkyl ester, etc. are mentioned.

[0024] Examples of polymers obtained by reaction of a tetracarboxylic acid derivative component and a diamine component include polyamic acid, polyamic acid ester, and polyimide which is an imidized polymer of the polyamic acid or polyamic acid ester. The reaction conditions for producing these polymers are not particularly limited, and a known method can be used.

[0025] The polymer used in the present invention may also be a polymer in which the main chain end is modified using a monofunctional compound relative to the tetracarboxylic acid derivative component and / or the diamine component. Examples of the monofunctional compound include monoamines, monoisocyanates, compounds having one acid anhydride group, compounds having one acid chloride group, and the like.

[0026] It should be noted that, in the present invention, "tetracarboxylic acid residue" refers to a structure derived from the tetracarboxylic acid derivative component, and refers to a tetravalent structure in which four carboxyl groups or groups derived from the carboxyl groups of the tetracarboxylic acid derivative are removed. In addition, "diamine residue" refers to a structure derived from the diamine component, and refers to a divalent structure in which two amino groups of the diamine are removed.

[0027] <Polymer A>

[0028] The polymer (A) is a polymer obtained by a (polycondensation) reaction of a tetracarboxylic acid derivative component with a diamine component containing a diamine represented by the following formula (1) and a diamine represented by the following formula (2).

[0029]

[0030] The diamine residue in the polymer (A) has at least two structures of a diamine residue derived from a diamine of the formula (1) and a diamine residue derived from a diamine of the formula (2).

[0031] In polymer (A), the diamine residue derived from the diamine of formula (1) is preferably 10 mol% or more, more preferably 20 mol% or more of all diamine residues in polymer (A). In addition, in polymer (A), the diamine residue derived from the diamine of formula (2) is preferably 30 mol% or more, more preferably 40 mol% or more of all diamine residues in polymer (A).

[0032] The polymer (A) may have a diamine residue derived from another diamine other than the diamines of formula (1) and formula (2). Examples of the other diamine include diamines represented by the following formula (4) (excluding the diamines of formula (1) and formula (2)).

[0033]

[0034] In formula (4), Y1 represents a divalent organic group, and two Rs each independently represent a hydrogen atom or an alkyl group having 1 to 5 carbon atoms.

[0035] Although (Y1-1) to (Y1-18) are shown below as preferred specific examples of Y1 in formula (4), the present invention is not limited thereto.

[0036]

[0037]

[0038] When the polymer (A) has a diamine residue derived from a diamine other than the diamine of formula (1) and formula (2), the total of the diamine residue derived from the diamine of formula (1) and the diamine residue derived from the diamine of formula (2) is preferably 50 mol% or more, more preferably 60 mol% or more, of all the diamine residues contained in the polymer (A).

[0039] In addition, from the viewpoint that when the liquid crystal orientation agent of the present invention is applied to a substrate, the polymer (A) tends to be biased toward the surface layer of the liquid crystal orientation film, thereby improving the orientation of the liquid crystal, it is preferred to use at least one of the diamines having a structure of the following formula (5) in which Y1 in the above formula (4) is used as the above-mentioned other diamine.

[0040]

[0041] In formula (5), D represents a protecting group which is detached by heating at preferably 80 to 250° C., particularly preferably 80 to 230° C. and replaced by a hydrogen atom, and * represents a linking site to another structure. Preferred examples of D include tert-butoxycarbonyl.

[0042] Preferred specific examples of Y1 having the structure of formula (5) are (5-1) to (5-9) below, but the present invention is not limited thereto. In the following structure, Boc represents a tert-butoxycarbonyl group.

[0043]

[0044] In the polymer (A), the residue of the diamine represented by the formula (4) is preferably 1 to 40 mol%, more preferably 5 to 30 mol%, of all the diamine residues in the polymer (A).

[0045] The structure of the tetracarboxylic acid residue in the polymer (A) is not particularly limited. In addition, the structure of the tetracarboxylic acid residue in the polymer (A) may be one type or a mixture of two or more types.

[0046] Hereinafter, (A-1) to (A-21) are shown as preferred structures of the tetracarboxylic acid residue in the polymer (A), but the present invention is not limited thereto.

[0047]

[0048]

[0049] The molecular weight of the polymer (A) is not particularly limited as long as a good coating film can be formed, and for example, the weight average molecular weight is preferably 2,000 to 500,000, more preferably 5,000 to 300,000, and further preferably 10,000 to 100,000. The number average molecular weight is preferably 1,000 to 250,000, more preferably 2,500 to 150,000, and further preferably 5,000 to 50,000.

[0050] <Polymer B>

[0051] The polymer (B) is a polymer obtained by reaction of a tetracarboxylic acid derivative component and a diamine component containing at least one diamine represented by the following formula (3).

[0052] H2N-Y2-NH2 (3)

[0053] In formula (3), Y2 is a divalent organic group having a nitrogen atom or a nitrogen-containing aromatic heterocycle bonded to an aromatic group.

[0054] (Y2-1) to (Y2-14) are shown below as particularly preferred structures of Y2, but the present invention is not limited thereto.

[0055]

[0056]

[0057] The structure of the diamine residue in the polymer (B) may be one type or a mixture of two or more types. However, at least one type is the structure of Y2 of the above formula (3).

[0058] In the polymer (B), the diamine residue as the structure of Y2 preferably accounts for 50 mol% or more, and more preferably 60 mol% or more, of all the diamine residues in the polymer (B).

[0059] The polymer (B) may also have a diamine residue derived from another diamine other than the diamine represented by formula (3). As the other diamine, the compound represented by formula (4) as the other diamine in the polymer (A) (wherein the diamine represented by formula (3) is excluded) can be used. The amount of the other diamine used in this case is also the same as that in the polymer (A).

[0060] The structure of the tetracarboxylic acid residue in the polymer (B) is not particularly limited. In addition, the structure of the tetracarboxylic acid residue in the polymer (B) may be one type or a mixture of two or more types.

[0061] As a preferred structure of the tetracarboxylic acid residue in the polymer (B), the preferred structures shown for the polymer (A) can be mentioned, but the present invention is not limited thereto.

[0062] The molecular weight of the polymer (B) is not particularly limited as long as a good coating film can be formed, and for example, the weight average molecular weight is preferably 2,000 to 500,000, more preferably 5,000 to 300,000, and further preferably 10,000 to 100,000. The number average molecular weight is preferably 1,000 to 250,000, more preferably 2,500 to 150,000, and further preferably 5,000 to 50,000.

[0063] <Liquid crystal alignment agent>

[0064] The content ratio of the polymer (A) to the polymer (B) in the liquid crystal aligning agent of the present invention is not particularly limited, and the content of the polymer (A) is preferably 10 to 50% by mass, and more preferably 20 to 40% by mass, relative to the total amount of the polymer (A) and the polymer (B). That is, the content of the polymer (B) is preferably 90 to 50% by mass, and more preferably 80 to 60% by mass, relative to the total amount of the polymer (A) and the polymer (B).

[0065] The liquid crystal aligning agent of the present invention may also contain other polymers other than polymer (A) and polymer (B). Other polymers are not particularly limited, and examples thereof include polymers having a main skeleton such as polyamic acid, polyamic acid ester, polyimide, polysiloxane, polyester, cellulose derivative, polyacetal, polystyrene derivative, poly(styrene-maleimide) derivative, and poly(meth)acrylate.

[0066] The liquid crystal alignment agent of the present invention may also contain components other than polymers. As components other than polymers, there can be listed: dielectrics or conductive substances for the purpose of changing the electrical properties such as the dielectric constant and conductivity of the liquid crystal alignment film; silane coupling agents for the purpose of improving the adhesion between the liquid crystal alignment film and the substrate; crosslinking compounds for the purpose of improving the hardness and density of the film when the liquid crystal alignment film is made; and imidization accelerators for the purpose of efficiently performing the imidization of polyamic acid when the coating film is fired.

[0067] The liquid crystal aligning agent of the present invention is a liquid crystal aligning agent for making a liquid crystal aligning film. From the viewpoint of forming a uniform film, it is preferably a coating solution in which the above-mentioned components are dissolved in an organic solvent. The concentration of the coating solution is appropriately changed according to the coating device used and the thickness of the liquid crystal aligning film to be obtained. From the perspective of forming a uniform and defect-free coating film, the concentration of the polymer is preferably 1% by mass or more, and from the perspective of the storage stability of the solution, the concentration of the polymer is preferably set to 10% by mass or less. The concentration of the particularly preferred polymer is 2 to 8% by mass.

[0068] The organic solvent used in the above-mentioned coating solution is not particularly limited as long as it uniformly dissolves the polymer component. If specific examples are listed, they can be listed as: N, N-dimethylformamide, N, N-dimethylacetamide, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, dimethyl sulfoxide, γ-butyrolactone, 1,3-dimethyl-imidazolidinone, methyl ethyl ketone, cyclohexanone, cyclopentanone, etc. Among them, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone or γ-butyrolactone is preferred. These solvents can also be used in combination of two or more.

[0069] In addition, in the composition for the purpose of film formation, in addition to the solvent as described above, a mixed solvent of a solvent that improves the coating property and the smoothness of the film surface is usually used, and in the liquid crystal alignment agent of the present invention, such a mixed solvent is also preferably used. Specific examples of the mixed organic solvent are listed in the following content, but are not limited to these examples.

[0070] For example, ethanol, isopropanol, 1-butanol, 2-butanol, isobutanol, tert-butanol, 1-pentanol, 2-pentanol, 3-pentanol, 2-methyl-1-butanol, isopentanol, tert-pentanol, 3-methyl-2-butanol, neopentyl alcohol, 1-hexanol, 2-methyl-1-pentanol, 2-methyl-2-pentanol, 2-ethyl-1-butanol, 1-heptanol, 2-heptanol, 3-heptanol, 1-octanol, 2-octanol, 2-ethyl-1-hexanol, cyclohexanol, 1-methylcyclohexanol, 2-methylcyclohexanol, 3-methylcyclohexanol, 1,2-ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,2-butylene glycol, 1,3-butylene glycol, 1 , 4-butanediol, 2,3-butanediol, 1,5-pentanediol, 2-methyl-2,4-pentanediol, 2-ethyl-1,3-hexanediol, dipropyl ether, dibutyl ether, dihexyl ether, dioxane, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, ethylene glycol dibutyl ether, 1,2-butoxyethane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, 4-hydroxy-4-methyl-2-pentanone, diethylene glycol methyl ethyl ether, diethylene glycol dibutyl ether, 2-pentanone, 3-pentanone, 2-hexanone, 2-heptanone, 4-heptanone, 3-ethoxybutyl acetate, 1-methylpentyl acetate, 2-ethylbutyl acetate, 2-ethylhexyl acetate, Ethylene glycol monoacetate, ethylene glycol diacetate, propylene carbonate, ethylene carbonate, 2-(methoxymethoxy)ethanol, ethylene glycol monobutyl ether, ethylene glycol monoisoamyl ether, ethylene glycol monohexyl ether, 2-(hexyloxy)ethanol, furfuryl alcohol, diethylene glycol, propylene glycol, propylene glycol monobutyl ether, 1-(butoxyethoxy)propanol, propylene glycol monomethyl ether acetate, dipropylene glycol, dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, dipropylene glycol dimethyl ether, tripropylene glycol monomethyl ether, ethylene glycol monomethyl ether acetate, ethylene glycol monoethyl ether acetate, ethylene glycol monobutyl ether acetate, ethylene glycol monoacetate, ethylene glycol diacetate, diethylene glycol monoethyl ether Acetate, diethylene glycol monobutyl ether acetate, 2-(2-ethoxyethoxy)ethyl acetate, diethylene glycol acetate, triethylene glycol, triethylene glycol monomethyl ether, triethylene glycol monoethyl ether, methyl lactate, ethyl lactate, methyl acetate, ethyl acetate, n-butyl acetate, propylene glycol acetate monoethyl ether, methyl pyruvate, ethyl pyruvate, methyl 3-methoxypropionate, methyl ethyl 3-ethoxypropionate, ethyl 3-methoxypropionate, 3-ethoxypropionic acid, 3-methoxypropionic acid, propyl 3-methoxypropionate, butyl 3-methoxypropionate, n-propyl lactate, n-butyl lactate, isoamyl lactate, solvents represented by the following formulas [D-1] to [D-3], and the like.

[0071]

[0072] (R in formula [D-1] and formula [D-2] represents an alkyl group having 1 to 3 carbon atoms, and R in formula [D-3] represents an alkyl group having 1 to 4 carbon atoms.)

[0073] Among the above, 1-hexanol, cyclohexanol, 1,2-ethylene glycol, 1,2-propylene glycol, propylene glycol monobutyl ether, diethylene glycol diethyl ether, 4-hydroxy-4-methyl-2-pentanone, ethylene glycol monobutyl ether or dipropylene glycol dimethyl ether are preferred. The type and content of such solvents are appropriately selected according to the coating device, coating conditions, coating environment, etc. of the liquid crystal alignment agent. In addition, these solvents can also be used in combination of two or more.

[0074] <Liquid crystal alignment film>

[0075] The liquid crystal alignment film of the present invention is obtained from the liquid crystal alignment agent of the present invention. If an example of a method for obtaining a liquid crystal alignment film from a liquid crystal alignment agent is given, it can be listed as a method of applying a liquid crystal alignment agent in the form of a coating liquid to a substrate, drying it, and firing it, and then performing an alignment treatment by a brushing treatment method or a photo-alignment treatment method.

[0076] As the substrate for coating the liquid crystal alignment agent, there is no particular limitation, and a glass substrate, a silicon nitride substrate, an acrylic substrate, a plastic substrate such as a polycarbonate substrate, etc. can be used. At this time, if a substrate having an ITO electrode or the like for driving the liquid crystal is used, it is preferred from the perspective of simplifying the process. In addition, in a reflective liquid crystal display element, if only a single-sided substrate is used, an opaque object such as a silicon wafer can also be used, and the electrode in this case can also use a light-reflecting material such as aluminum.

[0077] The coating method of the liquid crystal aligning agent is not particularly limited, and is generally industrially screen printing, gravure printing, flexographic printing, inkjet printing, etc. Other coating methods include dipping, roll coating, slit coating, spin coating, spray coating, etc., and these can be used according to the purpose.

[0078] After the liquid crystal alignment agent is applied to the substrate, the solvent is evaporated and fired by a heating unit such as a heating plate, a heat circulation oven, an IR (infrared) oven, etc. The drying and firing steps after the liquid crystal alignment agent is applied can select any temperature and time. In order to fully remove the contained solvent, the conditions of firing at 50 to 120°C for 1 to 10 minutes and then firing at 150 to 300°C for 5 to 120 minutes are generally listed.

[0079] Although the thickness of the liquid crystal aligning film after baking is not particularly limited, if it is too thin, the reliability of the liquid crystal display element may decrease, so it is preferably 5 to 300 nm, more preferably 10 to 200 nm.

[0080] The liquid crystal aligning film of the present invention is preferably used as a liquid crystal aligning film for a liquid crystal display element of a transverse electric field system such as an IPS system or an FFS system, and is particularly useful as a liquid crystal aligning film for a liquid crystal display element of an FFS system.

[0081] <Liquid crystal display device>

[0082] The liquid crystal display element of the present invention is prepared by preparing a liquid crystal cell by a known method after obtaining a substrate having a liquid crystal alignment film obtained from the above-mentioned liquid crystal alignment agent, and using the liquid crystal cell to prepare an element.

[0083] An example of a method for producing a liquid crystal cell is described below, but the present invention is not limited thereto.

[0084] First, a set of substrates having electrodes for driving liquid crystals are prepared. The electrodes can be, for example, ITO electrodes, which are patterned in a manner that enables the desired image display. In addition, conversion elements such as TFTs (Thin Film Transistors) can also be provided in each pixel portion constituting the image display. A liquid crystal alignment film is formed on the substrate as described above.

[0085] Next, a sealing material such as an ultraviolet-curable sealing material is arranged at a specified location on one of the two substrates on which a liquid crystal alignment film is formed, and after liquid crystals are further arranged at several specified locations on the surface of the liquid crystal alignment film, the other substrate is attached and crimped in a manner that the liquid crystal alignment film is opposed to each other, thereby pressing and spreading the liquid crystal on the front surface of the liquid crystal alignment film, and then ultraviolet rays are irradiated onto the entire surface of the substrate to cure the sealing material, thereby obtaining a liquid crystal unit.

[0086] In addition, as a process after forming a liquid crystal alignment film on a substrate, when a sealing material is arranged at a predetermined location on one substrate, an opening that can be filled with liquid crystal from the outside is pre-set, and after the substrates are attached without arranging liquid crystal, a liquid crystal material is injected into the liquid crystal cell through the opening provided in the sealing material, and then the opening is sealed with an adhesive to obtain a liquid crystal cell. The injection of the liquid crystal material can be a vacuum injection method or a method using a capillary phenomenon in the atmosphere.

[0087] In any of the above methods, in order to ensure a space for the liquid crystal material to fill the liquid crystal unit, it is preferred to use the following method: providing columnar protrusions on one substrate, dispersing spacers on one substrate, mixing spacers into the sealing material, or a combination of these methods.

[0088] As the above-mentioned liquid crystal material, nematic liquid crystal and smectic liquid crystal can be listed, among which nematic liquid crystal is preferred, and any one of positive liquid crystal material and negative liquid crystal material can be used. Next, a polarizing plate is set. Specifically, it is preferred to attach a pair of polarizing plates to the surface of the two substrates on the opposite side of the liquid crystal layer.

[0089] [Example]

[0090] The present invention will be specifically described below with reference to Examples, etc., but the present invention is not limited to these Examples. The abbreviations of the following compounds and solvents are as follows.

[0091] NMP: N-methyl-2-pyrrolidone, BCS: butyl cellosolve.

[0092] CA-1 to CA-4 are compounds of the following structural formulas, respectively. DA-1 to DA-6 are compounds of the following structural formulas, respectively.

[0093] AD-1: 3-glycidoxypropyltriethoxysilane, AD-2: a compound of the following structural formula.

[0094]

[0095] [Viscosity measurement]

[0096] The viscosity of the polymer solution was measured at a temperature of 25° C. using an E-type viscometer TVE-22H (manufactured by Toki Sangyo Co., Ltd.) with a sample volume of 1.1 mL and a conical rotor TE-1 (1°34′, R24).

[0097] <Polymer Synthesis>

[0098] (Synthesis example 1)

[0099] 2.86 g (10.0 mmol) of DA-1, 1.47 g (6.0 mmol) of DA-2, and 1.59 g (4.0 mmol) of DA-3 were weighed into a 100 mL eggplant flask equipped with a stirring device and a nitrogen inlet tube, and 53.2 g of NMP was added, and the mixture was stirred and dissolved while nitrogen was supplied. While stirring the diamine solution under water cooling, 4.20 g (19.3 mmol) of CA-1 was added, and 21.0 g of NMP was further added, and the mixture was stirred at 50° C. for 12 hours under a nitrogen atmosphere to obtain a polymer solution A-1 (concentration: 12.0 mass %, viscosity: 496 mPa·s).

[0100] (Synthesis example 2)

[0101] 3.19 g (16.0 mmol) of DA-4 and 0.79 g (4.0 mmol) of DA-5 were weighed into a 100 mL eggplant flask equipped with a stirring device and a nitrogen inlet tube, and 49.0 g of NMP was added, and the mixture was stirred and dissolved while nitrogen was supplied. While stirring the diamine solution under water cooling, 2.59 g (13.2 mmol) of CA-2 was added, and 13.9 g of NMP was further added, and the mixture was stirred at 23° C. for two and a half hours under a nitrogen atmosphere. Then, while stirring the solution under water cooling, 1.20 g (4.0 mmol) of CA-3 was added, and 7.0 g of NMP was further added, and the mixture was stirred at 23° C. for 12 hours under a nitrogen atmosphere, to obtain a polymer solution B-1 (concentration: 10.0 mass %, viscosity: 165 mPa·s).

[0102] (Synthesis example 3)

[0103] 3.67 g (18.4 mmol) of DA-4 and 0.70 g (4.6 mmol) of DA-6 were weighed into a 100 mL eggplant flask equipped with a stirring device and a nitrogen inlet tube, and 26.8 g of NMP was added, and the mixture was stirred and dissolved while nitrogen was supplied. While stirring the diamine solution under water cooling, 2.94 g (15.0 mmol) of CA-2 was added, and 14.5 g of NMP was further added, and the mixture was stirred at 23° C. for 30 minutes under a nitrogen atmosphere. Then, while stirring the solution under water cooling, 1.44 g (5.8 mmol) of CA-4 was added, and 8.2 g of NMP was further added, and the mixture was stirred at 50° C. for 12 hours under a nitrogen atmosphere to obtain a polymer solution B-2 (concentration: 15.0 mass %, viscosity: 352 mPa·s).

[0104] (Synthesis Example 4)

[0105] 3.19 g (16 mmol) of DA-4 and 0.79 g (4 mmol) of DA-5 were weighed into a 100 mL eggplant flask equipped with a stirring device and a nitrogen inlet tube, and 54.4 g of NMP was added, and the mixture was stirred and dissolved while nitrogen was supplied. While stirring the diamine solution under water cooling, 0.90 g (4.6 mmol) of CA-2 was added, and 15.5 g of NMP was further added, and the mixture was stirred at 23° C. for 30 minutes under a nitrogen atmosphere. Then, while stirring the solution under water cooling, 3.75 g (15.0 mmol) of CA-4 was added, and 7.8 g of NMP was further added, and the mixture was stirred at 50° C. for 12 hours under a nitrogen atmosphere to obtain a polymer solution B-3 (concentration: 10.0 mass %, viscosity: 218 mPa·s).

[0106] (Synthesis Example 5)

[0107] 5.73 g (20.0 mmol) of DA-1 was weighed into a 100 mL eggplant flask equipped with a stirring device and a nitrogen inlet tube, and 56.9 g of NMP was added, and the mixture was dissolved by stirring while nitrogen was supplied. While stirring the diamine solution under water cooling, 3.97 g (18.2 mmol) of CA-1 was added, and 14.2 g of NMP was further added, and the mixture was stirred at 50° C. for 12 hours under a nitrogen atmosphere to obtain a polymer solution C-1 (concentration: 12.0 mass %, viscosity: 505 mPa·s).

[0108] (Synthesis Example 6)

[0109] 4.13 g (14.4 mmol) of DA-1 and 1.43 g (3.6 mmol) of DA-3 were weighed into a 100 mL eggplant flask equipped with a stirring device and a nitrogen inlet tube, and 53.3 g of NMP was added, and the mixture was stirred and dissolved while nitrogen was supplied. While stirring the diamine solution under water cooling, 3.53 g (16.2 mmol) of CA-1 was added, and 13.3 g of NMP was further added, and the mixture was stirred at 50° C. for 12 hours under a nitrogen atmosphere to obtain a polymer solution C-2 (concentration: 12.0 mass %, viscosity: 498 mPa·s).

[0110] <Preparation of Liquid Crystal Alignment Agent>

[0111] Example 1

[0112] The polymer solution A-1 and the polymer solution B-1 were used to mix the polymer solution A-1 (7.5 g) and the polymer solution B-1 (21.0 g) in a manner such that the mass ratio of the two polymers was 30:70. NMP (5.1 g), BCS (12.5 g), an NMP solution containing 1 wt % AD-1 (3.0 g), and an NMP solution containing 10 wt % AD-2 (0.9 g) were added to the mixed solution while stirring, and further stirred at room temperature for 2 hours, thereby obtaining the liquid crystal aligning agent of the present invention.

[0113] Examples 2, 3 and Comparative Examples 1 to 4

[0114] According to the composition shown in the following Table 1, the same operation as in Example 1 was carried out to obtain liquid crystal aligning agents of Examples 2 and 3 of the present invention and liquid crystal aligning agents of Comparative Examples 1 to 4.

[0115] [Table 1]

[0116]

[0117] <Production of Liquid Crystal Cell>

[0118] The FFS-driven liquid crystal cell shown below was produced using the liquid crystal aligning agent obtained by the above-mentioned method.

[0119] [Configuration of FFS-driven liquid crystal unit]

[0120] In the case of a liquid crystal unit for fringe field switching (FFS) mode, a first glass substrate and a second glass substrate are set as a group, wherein the first glass substrate has a FOP (Finger on Plate) electrode layer formed of a common electrode in a planar shape, an insulating layer, and a pixel electrode in a comb-tooth shape on the surface, and the second glass substrate has a columnar spacer with a height of 4 μm on the surface, and an ITO film for anti-static is formed on the back. The above-mentioned pixel electrode has a comb-tooth shape, and the comb-tooth shape is a shape in which a plurality of electrode elements with a width of 3 μm are bent at an inner angle of 160° in the central part and arranged in parallel at intervals of 6 μm, and a pixel has a first area and a second area with a line connecting the bent parts of the plurality of electrode elements as a boundary.

[0121] It should be noted that the liquid crystal orientation film formed on the first glass substrate is oriented in a manner such that the direction dividing the inner angle of the pixel bending portion into equal parts is orthogonal to the orientation direction of the liquid crystal, and the liquid crystal orientation film formed on the second glass substrate is oriented in a manner such that the orientation direction of the liquid crystal on the first substrate is consistent with the orientation direction of the liquid crystal on the second substrate when manufacturing the liquid crystal unit.

[0122] [Production sequence of liquid crystal unit]

[0123] The liquid crystal alignment agent filtered through a filter with a pore size of 1.0 μm was applied to the surface of each of the glass substrates of the above group by spin coating, and dried on a hot plate at 80°C for 2 minutes. Then, it was calcined in a hot air circulation oven at 230°C for 30 minutes to obtain a substrate with a liquid crystal alignment film with a film thickness of 100 nm. The surface of the substrate with the liquid crystal alignment film was brushed with rayon cloth (YA-20R, manufactured by Yoshikawa Chemical Co., Ltd.) (roller diameter: 120 mm, roller speed: 1000 rpm, moving speed: 20 mm / sec, pressing length: 0.4 mm), and then irradiated with ultrasonic waves in pure water for 1 minute for cleaning. After removing water droplets by blowing, it was dried at 80°C for 15 minutes to obtain a substrate with a liquid crystal alignment film.

[0124] Next, a sealant was printed on one side of the substrate with a liquid crystal alignment film in the above group, and the other substrate was bonded to the liquid crystal alignment film surface in a manner that the brushing directions of each substrate were opposite to each other and parallel to each other, and the sealant was cured to produce an empty cell. Liquid crystal MLC-3019 (Merck) was injected into the empty cell by a reduced pressure injection method, and the injection port was sealed to obtain an FFS driven liquid crystal cell. Then, the obtained liquid crystal cell was heated at 120°C for 1 hour, and various evaluations were performed after it was left overnight.

[0125] <Characteristics evaluation of liquid crystal cell>

[0126] The characteristics of the liquid crystal cell produced in the above were evaluated as follows.

[0127] [Charge storage amount]

[0128] The FFS-driven liquid crystal cell produced above was placed between two polarizing plates arranged in a manner such that the polarization axes were orthogonal, and the LED backlight was irradiated from below the two polarizing plates while the pixel electrode and the opposing electrode were short-circuited to be at the same potential, and the angle of the liquid crystal cell was adjusted so that the brightness of the LED backlight transmission light measured on the two polarizing plates was minimized. This evaluation was performed under the temperature condition that the temperature of the liquid crystal cell was 23°C.

[0129] Next, while applying an AC voltage of 30 Hz to the liquid crystal unit, the V-T curve (voltage-transmittance curve) was measured, and the AC voltage values ​​at which the relative transmittance became 23% and 100% were calculated as the driving voltage. Next, in order to eliminate the influence of charging, an AC voltage of 1 kHz and 20 mV was applied to the liquid crystal unit at 23°C for 30 minutes.

[0130] Then, an AC voltage is applied for 45 minutes until the relative transmittance reaches 100%. During this period, the minimum offset voltage value is measured every 3 minutes, and the change from the start of the measurement to 45 minutes is calculated as the charge accumulation amount. The minimum offset voltage value refers to the DC voltage value at which the flicker is the smallest when the V-F curve (voltage-flicker curve) is measured when the AC voltage with a relative transmittance of 23% is applied. The reason for using an AC voltage with a relative transmittance of 23% is that this AC voltage value corresponds to an area where the brightness changes greatly with respect to the voltage, so it is appropriate to evaluate the accumulated charge through the brightness.

[0131] The accumulated charge affects the display as a disorder of the liquid crystal orientation and an afterimage, and the display quality level of the liquid crystal element is significantly reduced. Therefore, it can be said that the smaller the charge accumulation amount generated during driving, the better. Specifically, when the charge accumulation amount is less than 100mV, it is evaluated as "○", and when the charge accumulation amount is more than 100mV, it is evaluated as "×".

[0132] [Storage charge relaxation characteristics]

[0133] The FFS-driven liquid crystal unit produced above was set between two polarizing plates arranged in a manner that the polarization axes were orthogonal. The LED backlight was irradiated from below the two polarizing plates while the pixel electrode and the opposing electrode were short-circuited to the same potential. The angle of the liquid crystal unit was adjusted in such a way that the brightness of the LED backlight transmission light measured on the two polarizing plates was minimized. This evaluation was performed under the temperature condition that the temperature of the liquid crystal unit was 23°C. In order to eliminate the influence caused by charging, the liquid crystal unit was evaluated after applying an AC voltage of 20mV with a frequency of 1kHz for 30 minutes.

[0134] Next, while applying an AC voltage with a frequency of 30 Hz to the liquid crystal unit, the V-T curve (voltage-transmittance curve) was measured, and the AC voltage value at which the relative transmittance became 23% was calculated as the driving voltage. This AC voltage value corresponds to the region where the brightness changes greatly with respect to the voltage, so it is appropriate to evaluate the stored charge through the brightness.

[0135] After applying an AC voltage of 30 Hz to a relative transmittance of 23% for 5 minutes, a DC voltage of +1.0 V was superimposed and the device was driven for 30 minutes. The DC voltage was then cut off and only an AC voltage of 30 Hz was applied again to a relative transmittance of 23% for 30 minutes.

[0136] The faster the relaxation of the accumulated charge, the faster the charge accumulation to the liquid crystal unit when the DC voltage is superimposed. Therefore, the relaxation characteristics of the accumulated charge are evaluated by the time required for the relative transmittance to decrease from a state of more than 30% to 23% just after the DC voltage is superimposed. It can be said that the shorter the time, the better the relaxation characteristics of the accumulated charge. Specifically, the time from the application time point of the DC voltage to the time when the relative transmittance decreases to less than 30% is digitized. In the case of less than 20 minutes and the relative transmittance decreases to less than 30%, it is evaluated as "○", and the case of more than 20 minutes is evaluated as "×".

[0137] [Afterimage characteristics based on long-term AC drive]

[0138] The FFS-driven liquid crystal cell prepared above was subjected to an AC voltage of ±5 V at a frequency of 60 Hz for 120 hours at a constant temperature of 60° C. Then, the pixel electrode and the counter electrode of the liquid crystal cell were short-circuited and left at room temperature for one day.

[0139] Regarding the liquid crystal cell subjected to the above-described processing, the deviation between the alignment direction of the liquid crystal in the first region and the alignment direction of the liquid crystal in the second region of the pixel in a state where no voltage is applied is calculated as an angle.

[0140] Specifically, a liquid crystal unit is placed between two polarizing plates arranged with their polarization axes orthogonal to each other, the backlight is turned on, and the configuration angle of the liquid crystal unit is adjusted so that the intensity of transmitted light in the first area of ​​the pixel is minimized. Next, the rotation angle required to rotate the liquid crystal unit so that the intensity of transmitted light in the second area of ​​the pixel is minimized is calculated.

[0141] It can be said that the smaller the rotation angle is, the better the afterimage characteristics due to long-term AC driving are. Specifically, when the rotation angle is less than 0.5 degrees, it is evaluated as "○", and when the rotation angle is greater than 0.5 degrees, it is evaluated as "×".

[0142] [Voltage holding ratio]

[0143] For the FFS-driven liquid crystal unit produced above, a voltage of 1 V was applied to the liquid crystal display element for voltage holding rate evaluation at an application time of 60 microseconds and an interval of 1667 milliseconds, and the voltage holding rate (%) from the release of the application to 1667 milliseconds was measured at 60° C. Specifically, when the voltage holding rate is 95% or more, it is evaluated as "○", and when the voltage holding rate is less than 95%, it is evaluated as "×".

[0144] <Evaluation Results>

[0145] The evaluation results of the liquid crystal cell using each liquid crystal aligning agent of the above-mentioned Example and Comparative Example are shown in Table 2 below.

[0146] [Table 2]

[0147]

[0148] It was found that the liquid crystal display element using the liquid crystal aligning agent of the present invention has a small amount of accumulated charge and good relaxation characteristics of accumulated charge.

[0149] It should be noted that all the contents of the specification, claims, and abstract of Japanese Patent Application No. 2018-229216 filed on December 6, 2018 are incorporated herein by reference and incorporated as a disclosure of the specification of the present invention.

Claims

1. A liquid crystal alignment agent, wherein: Containing the following polymer A and polymer B, The polymer A is a polymer obtained by reaction of a tetracarboxylic acid derivative component with a diamine component including a diamine represented by the following formula (1) and a diamine represented by the following formula (2). The diamine residues derived from the diamine of formula (1) in the polymer A account for 10 mol% or more of all the diamine residues in the polymer A, and the diamine residues derived from the diamine of formula (2) account for 30 mol% or more of all the diamine residues in the polymer A, The polymer B is a polymer obtained by reaction of a tetracarboxylic acid derivative component with a diamine component containing at least one of the diamines represented by the following formula (3). H2N—Y2—NH2(3) In the formula, Y2 is a divalent organic group having a nitrogen atom or a nitrogen-containing aromatic heterocycle bonded to an aromatic group.

2. The liquid crystal alignment agent according to claim 1, wherein The diamine component in the polymer A and / or polymer B further contains at least one of the diamines represented by the following formula (4): In the formula, Y1 represents a divalent organic group, and two Rs each independently represent a hydrogen atom or an alkyl group having 1 to 5 carbon atoms.

3. The liquid crystal alignment agent according to claim 2, wherein: The diamine component in the polymer A contains: Y1 in the formula (4) is a diamine having a divalent organic group having a structure of the following formula (5), In the formula, D represents a protecting group which is detached by heating and replaced by a hydrogen atom, and * represents a linking site to another structure. 4 . The liquid crystal aligning agent according to claim 1 , wherein The structure of the tetracarboxylic acid residue of the polymer A is at least one selected from the following structures (A-15) to (A-21), 5. The liquid crystal aligning agent according to any one of claims 1 to 3, wherein The content of the polymer A is 10 to 50% by mass and the content of the polymer B is 90 to 50% by mass relative to the total amount of the polymer A and the polymer B.

6. The liquid crystal aligning agent according to any one of claims 1 to 3, wherein The liquid crystal alignment agent is used for a liquid crystal display element of a transverse electric field driving mode.

7. The liquid crystal alignment agent according to claim 6, wherein: The transverse electric field driving method is the FFS driving method. 8 . A liquid crystal aligning film obtained from the liquid crystal aligning agent according to claim 1 . 9 . A liquid crystal display element comprising the liquid crystal alignment film according to claim 8 .

10. The liquid crystal display element according to claim 9, wherein The liquid crystal display element is driven by a transverse electric field.

11. The liquid crystal display element according to claim 10, wherein The liquid crystal display element adopts FFS driving mode.

Citation Information

Patent Citations

  • Liquid crystl orientating agent and liquid crystal display element using it

    WO2004053583A1

  • Liquid crystal aligning agent, liquid crystal alignment film and liquid crystal display element

    WO2018062440A1